Asas Kepentingan Umum dalam Pengadaan Tanah untuk Kepentingan Negara - Dede Yusuf; Suwari Akhmaddhian (Universitas Kuningan, 2019)
Legal arrangements regarding land acquisition for public use in Indonesia have undergone a process of development since the unification of the Basic Agrarian Law No. 5 of 1960. However, in practice this provision has caused many problems that cannot be carried out effectively. Then the government issued Presidential Decree Number 55 of 1993, as revoked by Presidential Regulation Number 36 of 2005 concerning the release or transfer of land rights, which was then revised by Presidential Regulation Number 65 of 2006. Various problems existed in the acquisition of land for development for public use tried to be minimized through these regulations. Even though changes have been made to perfect the laws and regulations regarding land acquisition for development in the public interest in order to provide justice and welfare for the community, but there are still some juridical issues in the laws and regulations that escaped the attention of the drafters of the laws and regulations. invitation, which includes formal juridical aspects and material juridical aspects.Keywords: Principle of Public interest, land acquisition. AbstrakPengaturan hukum tentang pengadaan tanah untuk kepentingan umum di Indonesia telah mengalami proses perkembangan sejak unifikasi Undang-Undang Pokok Agraria Nomor 5 Tahun 1960. Namun dalam praktiknya ketentuan ini banyak menimbulkan masalah sehingga tidak dapat berjalan dengan efektif. Kemudian pemerintah mengeluarkan Keputusan Presiden Nomor 55 Tahun 1993, sebagaimana dicabut dengan Peraturan Presiden Nomor 36 Tahun 2005 mengenai pelepasan atau penyerahan hak atas tanah, yang kemudian direvisi oleh Peraturan Presiden Nomor 65 Tahun 2006. Berbagai masalah yang terdapat dalam pengadaan tanah bagi pembangunan untuk kepentingan umum telah coba diminimalisir melalui peraturan-peraturan tersebut. Meskipun telah diadakan perubahan-perubahan untuk menyempurnakan peraturan perundang-undangan mengenai pengadaan tanah bagi pembangunan untuk kepentingan umum dalam rangka memberikan keadilan dan kesejahteraan bagi masyarakat, namun tetap saja ada beberapa permasalahan yuridis dalam peraturan perundang-undangan tersebut yang luput dari perhatian penyusun peraturan perundang-undangan, yaitu meliputi aspek yuridis formal dan aspek yuridis materiil.Kata Kunci : Asas Kepentingan umum, pengadaan tanah.